Flazasulfuron Tank Mixtures with Amicarbazone for Annual Bluegrass Control in Seashore Paspalum. Issue 1 (2nd January 2014) - Johnston, Christopher R.; McCullough, Patrick E.
Abstract : Flazasulfuron may be safely applied to actively growing seashore paspalum ( Paspalum vaginatum Sw.), but applications for annual bluegrass control in late winter or spring could be injurious. A 3‐year field experiment was conducted to evaluate tank mixtures of flazasulfuron with amicarbazone at turf dormancy or partial greenup to determine if combinations could enhance annual bluegrass control and mitigate seashore paspalum injury compared to exclusive treatments. Single applications of flazasulfuron at 26 g a.i. ha −1 at both timings provided good (80 to 89%) to excellent (>90%) control of annual bluegrass in 2 of 3 years, while sequential applications provided ≥86% control at both timings in all 3 years. Tank mixtures of flazasulfuron at 26 g ha −1 plus amicarbazone at 196 g ha −1 significantly improved annual bluegrass control from flazasulfuron alone at 26 g ha −1 at both timings in 2 of 3 years. Amicarbazone tank mixtures did not improve annual bluegrass control from flazasulfuron at 52 g ha −1 alone at either timing. Late winter applications of amicarbazone at 196 g ha −1 alone provided poor annual bluegrass control (<70%) in 2 of 3 years while applications at turf greenup provided ≥88% control in all 3 years. Pronamide provided fair control (70 to 78%) and excellent control (≥90%) of annual bluegrass in 2 of 3 years when applied at dormancy or at greenup, respectively. All flazasulfuron treatments caused 36 to 54% injury when applied at greenup but single applications at dormancy caused 13 to 29% injury. Amicarbazone and pronamide alone never injured seashore paspalum greater than 17% at both application timings and treatments at greenup provided the best combinations of annual bluegrass control and turf tolerance.